Sodium Valproate Enhances the Urethane-Induced Lung Adenomas and Suppresses Malignization of Adenomas in Ovariectomized Female Mice - Donatas Stakisaitis; Raminta Mozuraite; Nomeda Juodziukyniene; Janina Didziapetriene; Saule Uleckiene; Paulius Matusevicius; Angelija Valanciute (International Journal of Endocrinology)
In the present study, the possible effect of sodium valproate (NaVP) on urethane-induced lung tumors in female mice has been evaluated. BALB/c mice (n=60; 4–6 weeks old, females) were used in the following groups: (1) urethane-treated; (2) urethane-NaVP-treated; (3) only NaVP-treated; (4) control. In the same groups, ovariectomized female mice (n=60) were investigated. Urethane was given intraperitoneally, with a total dose of 50 mg/mouse. In NaVP-treated mice groups, 0.4% aqueous solution of NaVP was offered to mice ad libitum. The duration of the experiment was 6 months. The number of tumors per mouse in ovariectomized mice and in those treated with urethane and NaVP was significantly higher than in mice treated with urethane only (8.29±0.58 versus 6.0±0.63, p<0.02). No significant difference in the number of tumors per mouse was revealed while comparing the nonovariectomized urethane- and urethane-NaVP-treated groups (p=0.13). A significant decrease of adenocarcinoma number in ovariectomized mice treated with a urethane-NaVP as compared with ovariectomized mice treated with urethane only was found (p=0.031). NaVP together with low estrogen may have a protective effect on the malignization of adenomas in ovariectomized mice.